Perbandingan Cake Foundation dan Liquid Foundation untuk Kulit Berminyak pada Rias Wajah sehari-hari - Jeny Cartika Tonapa; Mitra Lusiana (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2025)
This study aims to compare the use of cake foundation and liquid foundation in terms of smoothness and durability of daily makeup for oily skin. The research employed a pre-experimental method with a one-shot case study design. The participants consisted of six students from the Department of Cosmetology, Universitas Negeri Padang, class of 2023, who have oily skin types. The evaluation was carried out by seven skilled panelists from educational institutions, the beauty industry, and student representatives. Data were collected through observation and documentation, and then analyzed using a T-test. The findings revealed that the application of cake foundation resulted in higher levels of smoothness and durability compared to liquid foundation. The average smoothness score for cake foundation was 3.43, while liquid foundation scored 3.05. In terms of durability, cake foundation achieved an average score of 3.52, whereas liquid foundation scored 2.67. Based on the hypothesis testing, a significance value of 0.035 < 0.05 was obtained, indicating a significant difference between the application of cake foundation and liquid foundation on the smoothness and durability of daily makeup for oily skin.